Measurement Invariance and Latent Mean Differences in Computational Thinking, Cultural Insight, and Numeracy Skills among Thai and Indonesian University Students - Afifi Lateh; Yeni Rakhmawati; Meechai Wongdaeng; Chatthida Yukong; Tawatchai Sritep; Mohammad Archi Maulyda (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2026)
This study examines the measurement structure and cross-national differences of university students' computational thinking, cultural insight, and numeracy skills in Thailand and Indonesia. It has 624 respondents including 338 Thai and 286 Indonesian undergraduate students. Data were analysed using the multi-group confirmatory factor analysis to test for measurement invariance between both national groups prior to latent means comparison. The results showed that the three-factor measurement model yielded an acceptable fit to the data. Tests of measurement invariance supported configural and metric invariance, with partial scalar invariance found between the two groups. Cross-national differences were significant according to latent mean comparisons. Thai students showed more computational thinking and cultural insight, while Indonesian students displayed better numeracy skills. The results show the need for analytical, intercultural and quantitative skills in higher education educational systems to channel the development of future generations into effective solutions